Model Kepemimpinan Perdana: Analisis Eksegetis 1 Timotius 3:1-7 Dan Implikasinya Bagi Manajemen Kepemimpinan Kristen Kontemporer - Lafa Diana; Paulus Kunto Baskoro (Sekolah Tinggi Teologi Injili Indonesia Ambon, 2026)
Leadership within the ecclesiastical context has become a crucial subject in theological and Christian management discourse, especially regarding holistic qualification standards. Previous studies on Christian leadership have tended to focus on charisma and administrative competency while neglecting the moral character and relational quality as articulated in Scripture. This study aims to exegetically examine 1 Timothy 3:1-7 in order to formulate a comprehensive model of exemplary leadership and its implications for contemporary Christian leadership management. The methodology employed is biblical exegesis through grammatical, syntactical, and historical-theological analysis of the Greek text. The findings reveal that the text presents three inseparable dimensions of leadership: moral character (anepilémptos), managerial competence (didaktikos), and social reputation (marturían kalén). This study contributes to constructing an integrated Christian leadership model encompassing spiritual, relational, and managerial dimensions as a theological foundation for developing contemporary church leaders.